The Influence of Process Parameters on the Morphology of Laser Wire Additive Manufacturing - Chenxiao Yan; Hongbiao Han; Jiayang Hu; Peng Zhang; Jun Li (International Journal of Optics)
Laser additive manufacturing (LAM), as direct forming manufacturing technology, can be used to repair, clad, and process components; it is regarded as a revolutionary breakthrough in manufacturing technology. As an important branch of LAM, laser wire additive manufacturing (LWAM) has received extensive attention. However, there is a notable lack of systematic research clarifying the interdependent relationship between the process parameters and the deposited layer morphology of LWAM for 316L stainless steel. In this paper, a complex 6-factor 4-level 316L stainless steel LWAM orthogonal experimental design was conducted with characteristics such as laser oscillation mode, oscillation amplitude, defocusing amount, laser power, scanning speed, and wire feeding speed. Furthermore, the morphological changes of the LWAM deposition layer under different process parameters were analyzed and the interaction effect of process variations on molten pool morphology was investigated by range analysis. Overall, it helps to find a balance between the desired bead shape, surface finish, and molten pool porosity defects to achieve the desired results of the additive demand.